Analysis of the pedagogical perspective of the MOOCs available in Portuguese - Lemos-de-Carvalho-Júnior, Giovani; Raposo-Rivas, Manuela; Cebrián-de-la-Serna, Manuel; Sarmiento-Campos, José A. (My University, 2018)
After an initial stage of exponential growth in MOOCs, a need has arisen of to address several different aspects of these innovations in order to understand and develop them from different perspectives, such as this one, with the analysis of pedagogical dimensions aimed at improving course design. This paper presents an updated review of the literature and proposes five research lines for an in-depth approach. This study is part of a broader research project1 and here analyses 356 MOOCs delivered in Portuguese by 16 different platforms. The research design is quantitative, non-experimental and transversal. An adaptation of the MOOC Educational and Interactive Indicators Instrument —INdiMOOC-EdI— was used in the data collection process. The reliability and internal consistency analysis of that adaptation for the whole sample resulted in a Cronbach alpha score of 0.731. The data obtained enable us to classify the existing MOOCs in Portuguese according to descriptive, formative, and interactive components. These different types correlate with the quality indices, being negative in the first dimension (descriptive) and positive in the second and third ones (formative and interactive).
Keywords: Enseñanza - Innovaciones tecnológicas; Mooc; Pedagogical design; Instructional design; Content analysis